Pickup Strategy based on Table Tennis Pickup Robot - Huang, Hongxue (Highlights in Science, Engineering and Technology, 2024)
Due to the injuries and inconvenience that picking balls caused, a number of ball pickup robot showed up in recent years. The existing ball pickup robots have a common problem that is they can’t complete the picking task at a fast speed for they are set to pick up all the balls. Put it another way, when facing multiple balls, their efficiency decreases to some extent. Different from their idea of picking all the balls, the new strategy in this paper aims to propose can balance efficiency and the degree of completion (picking enough balls) for the ball pick up robot. Taking table tennis as example, this paper first introduces the necessary hardware. And then it introduces the principle of detection, which is color recognition, and path planning, after which the collection structure is presented. Ultimately, the mode of data transmission is indicated. This paper offers a new way of thinking about ball pickup strategies for ball pickup robots, which contributes to the development of related robots.